Growth and challenges of E-commerce in Bangladesh: a study on priyoshop.com ltd - Chowdhury, Mahtabashamin (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.